A quick hemostatic powder with self-gelling antibacterial and adjustable adhesion and preparation method thereof
By using materials such as quaternized cellulose, polyethylene glycol, aminated montmorillonite and tannin, the shortcomings of existing hemostatic materials in functionalization and application are solved, and a multifunctional hemostatic effect of self-geling, antibacterial and adjustable adhesion is achieved.
Patent Information
- Application Number
- CN202410831762.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-06-26
AI Technical Summary
Existing hemostatic materials have insufficient functionalization and application, making it difficult to achieve rapid and effective hemostatic in traumatic or battlefield environments, especially in organs with irregular shapes, arterial or venous bleeding and incompressible.
A rapid hemostatic powder with self-gel, antibacterial and adjustable adhesion is constructed using materials such as quaternary ammonium cellulose, polyethylene glycol, aminated montmorillonite and tannin acid. The self-gel performance is achieved through non-covalent reversible physical interactions between molecules and the movement of polymer chains. Tannins provide antibacterial activity and quaternary ammonium cellulose enhance adhesion.
It achieves rapid hemostasis, excellent biocompatibility and versatility, and can quickly absorb blood on irregular wounds, forming a dense hydrogel barrier, significantly improving the hemostasis speed and effect.
Smart Images

Figure CN118649279B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical engineering hemostatic materials, and specifically discloses a quick hemostatic powder with self-gelling, antibacterial and adjustable adhesion properties and a preparation method thereof. Background Art
[0002] Excessive bleeding in the body may disrupt the homeostasis of the human body's internal environment and lead to endocrine disorders. Uncontrolled bleeding may lead to serious complications, including hypothermia, hypotension, acidosis, organ dysfunction, and even death. The endogenous hemostatic mechanism is not sufficient to achieve rapid and effective hemostasis in trauma or battlefield environments. Therefore, the development of effective hemostatic materials is an urgent clinical issue, especially for organs with irregular shapes, arterial or venous bleeding, and incompressible organs. An ideal hemostatic material has the following requirements: rapid hemostatic ability, excellent adhesion and antibacterial properties, good blood compatibility and biocompatibility, easy to use, low cost, etc.
[0003] At present, many hemostatic materials have been developed at home and abroad, including hydrogels, sponges, gauze and powders. Hemostatic sponges and bandages often use the concentration of coagulation factors and the aggregation of blood cells to accelerate the formation of clots and achieve hemostasis. However, due to its small specific surface area, large volume, poor adhesion and low fluidity, its application in incompressible wounds is greatly limited. The high specific surface area and good fluidity of hemostatic powder enable it to reach irregular, small and narrow bleeding sites. However, the lack of cross-linking structure between traditional hemostatic powders makes it difficult to form a stable physical barrier at the wound, and even dissolves in the blood. At the same time, it lacks the ability to adhere, is easily washed away by the blood at the wound, and falls off from the wound surface, thus failing to realize its ability as a hemostatic powder. Hydrogel is a three-dimensional hydrophilic polymer network prepared by chemical / physical cross-linking. In the process of designing and preparing hydrogels, researchers adjusted their physical and mechanical properties to match the biological tissues to which they are applied. Hydrogels with high adhesion can form a physical barrier on the wound surface to reduce bleeding. However, the interfacial water on the wound surface and the continuous blood flow in the wound surface will affect the adhesion between the hydrogel and the tissue, thereby weakening the hemostatic property of the hydrogel.
[0004] Even though the hemostatic effects of the currently developed hemostatic materials have been greatly improved compared to traditional hemostatic materials, they still have limitations in application and cannot well meet the current demand for multifunctional hemostatic materials. Therefore, researchers are eager to prepare biomedical hemostatic materials with rapid hemostatic performance, excellent biocompatibility, and multifunctionality. Summary of the invention
[0005] The technical problem to be solved by the present invention is: how to overcome the deficiencies in the functionalization and application limitations of existing hemostatic materials and provide a hemostatic material with self-gelling, rapid hemostatic performance, switchable strong adhesion and strong antibacterial ability.
[0006] The technical scheme adopted by the present invention is: a quick hemostatic powder with self-gelling antibacterial and adjustable adhesion, the quick hemostatic powder comprises quaternary ammonium cellulose, polyethylene glycol, amino montmorillonite and tannic acid, wherein the quaternary ammonium cellulose, polyethylene glycol and amino montmorillonite constitute a matrix network, tannic acid is used as a physical cross-linking agent to provide interface adhesion, and the strong non-covalent reversible physical interaction between molecules and the movement of polymer chains after the hemostatic powder is hydrated make the hemostatic powder have self-gelling properties; the physical Cross-linking is the key interaction in the adhesion matrix that makes it adhesive; the phenolic hydroxyl tannic acid in the quick hemostatic powder can inhibit the synthesis of bacterial cell walls and destroy cell membranes, and it has strong antibacterial activity. The cellulose with positively charged quaternary ammonium groups in the quick hemostatic powder can bind to bacterial cell walls through electrostatic effects, change the permeability of bacterial cell membranes, inhibit bacterial growth, and even kill bacteria, making it have antibacterial properties; 5wt% urea solution can replace the hydrogen bonds between tannic acid and polyethylene glycol, resulting in the destruction of adhesion properties.
[0007] A method for preparing a self-gelling antibacterial and adjustable adhesive rapid hemostatic powder comprises the following steps: mixing a precursor solution and a tannic acid solution, stirring them uniformly (rapid stirring at 200 to 300 r / min for 10 to 15 minutes), overnight, collecting the precipitated hydrogel, pre-freezing it overnight, freezing it in a freeze dryer, obtaining a dry solid, grinding it, and sieving it to obtain a composite hemostatic powder.
[0008] The precursor solution is a mixed solution of cellulose derivatives, polyethylene glycol and montmorillonite derivatives.
[0009] The cellulose derivative is quaternized cellulose, and the montmorillonite derivative is amination montmorillonite.
[0010] The aminated montmorillonite and deionized water are mixed and ultrasonically dispersed for 30 minutes (power 100-200W) to obtain a dispersion; quaternary ammonium cellulose, polyethylene glycol and deionized water are weighed separately and stirred (quick stirring at 200-300r / min for 10-15min) to obtain a mixture; then the montmorillonite dispersion and the mixture are fully stirred to obtain a precursor solution.
[0011] The method for preparing the aminated montmorillonite comprises the following steps: adding 3-aminopropyltriethoxysilane to the crushed montmorillonite, stirring until the reaction is complete, adding deionized water to terminate the reaction, washing with deionized water and ethanol alternately, taking out, and drying at 60-80° C. to constant weight to obtain the aminated montmorillonite.
[0012] When 3-aminopropyltriethoxysilane is added to the crushed montmorillonite, 1 g of montmorillonite corresponds to 5 mL of 3-aminopropyltriethoxysilane.
[0013] The amination montmorillonite and deionized water are mixed at a mass ratio of 1:50, the quaternized cellulose and deionized water are mixed at a mass ratio of 1:50, and the polyethylene glycol and deionized water are mixed at a mass ratio of 3:20, and the molecular weight of the polyethylene glycol is 10000.
[0014] The concentration of quaternary ammonium cellulose is 2 wt %, the concentration of polyethylene glycol is 15 wt %, the concentration of tannic acid is 15 wt %, and the mass ratio of quaternary ammonium cellulose, polyethylene glycol, montmorillonite and tannic acid is 1:1:1:3.
[0015] The pre-freezing overnight and freezing treatment in a freeze dryer refers to pre-freezing at -10 to -20°C for 48 hours to obtain a pre-frozen hydrogel, placing it in a freeze dryer, and freeze-drying it for 20 to 24 hours at a temperature of -50 to -60°C and a vacuum degree of 10 to 20 Pa.
[0016] The beneficial effects of the present invention are as follows: the present invention utilizes a chemical reaction method to prepare aminated montmorillonite, which, as an excellent silicate hemostatic material, can exert hemostatic activity through surface negative charges and activate the coagulation system, but its potential metabolic toxicity leads to limited application in the field of hemostasis. The surface modification of aminated montmorillonite not only retains the original hemostatic ability of montmorillonite, but also enables it to interact with the phenolic hydroxyl groups of tannic acid to form hydrogen bonds, so that the montmorillonite is uniformly dispersed in the hydrogel.
[0017] The invention constructs a novel multifunctional hemostatic powder composed of quaternary ammonium cellulose, tannic acid, polyethylene glycol and amino montmorillonite by simple physical mixing. The powder has good hemostatic effect, self-gel, adjustable adhesion, biocompatibility and antibacterial properties. The quaternary ammonium cellulose, polyethylene glycol and amino montmorillonite in the invention provide a matrix network for the hemostatic powder, while the tannic acid acts as a physical cross-linking agent and provides interface adhesion. The strong non-covalent reversible physical interaction between molecules and the movement of polymer chains after the powder is hydrated make the hemostatic powder have self-gel properties. Therefore, when hydrated or applied to bleeding wounds, the hemostatic powder can quickly absorb blood in situ, concentrate coagulation factors, and form a flexible and dense hydrogel as a powerful physical barrier against blood pressure, which is more suitable for irregular wounds and achieves rapid hemostasis. The quaternary ammonium cellulose not only has antibacterial properties, but also maintains the original excellent properties of cellulose, such as the ability to quickly start the endogenous hemostatic pathway, excellent biocompatibility and water absorption properties. Tannin is a non-toxic polyphenolic compound rich in pyrogallol and catechol. It can physically crosslink with carboxyl, amino and hydroxyl groups in polysaccharides, and can also interact with a variety of polymers to form strong hydrogen bond interactions. In addition, since phenolic hydroxyl groups show negative charges in water environments, polysaccharides with positively charged nitrogen functional groups can bind to polyphenols through electrostatic interactions. Polyethylene glycol is a polymer with good water solubility, adhesion properties and rich ether groups, and has good biocompatibility. Montmorillonite, as an excellent silicate hemostatic material, can exert hemostatic activity through surface negative charges and activate the coagulation system. The surface-modified amino montmorillonite not only retains the original hemostatic ability of montmorillonite, but also enables it to interact with the phenolic hydroxyl groups of tannic acid to form hydrogen bonds. Most importantly, the physical interaction mediated by tannic acid is reversible, which has important potential for constructing multifunctional self-gel hemostatic powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a scanning electron microscope image of the hemostatic powder in Example 1 of the present invention;
[0019] Figure 2 This is a scanning electron microscope image of the hemostatic powder in Example 2 of the present invention;
[0020] Figure 3 This is a scanning electron microscope image of the hemostatic powder in Example 3 of the present invention;
[0021] Figure 4 The diagrams are the tissue adhesion test diagrams of the three hemostatic powders produced in Examples 1, 2 and 3 of the present invention, wherein a is the adhesion energy diagram and b is the bursting pressure diagram;
[0022] Figure 5 This is an antibacterial experimental diagram of the present invention;
[0023] Figure 6The in vitro coagulation absorbance assay of the present invention;
[0024] Figure 7 The biocompatibility test diagram of the hemostatic powder of the present invention is shown in Figure 1, wherein a is an absorbance diagram and b is a cell culture diagram;
[0025] Figure 8 These are experimental diagrams of in vivo hemostasis models of the hemostatic powder of the present invention, wherein a is a mouse liver injury bleeding model, and b is a mouse tail amputation bleeding model. DETAILED DESCRIPTION
[0026] In order to make the technical solutions and advantages of the present invention clearer, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. Obviously, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. Example 1
[0027] This embodiment provides a preparation method of quaternary ammonium cellulose / tannic acid composite powder, which comprises the following steps:
[0028] The quaternary ammonium cellulose and tannic acid were rapidly stirred at 200-300 r / min for 10-15 min at room temperature, and dissolved in deionized water, respectively, with final concentrations of 2 wt% and 15 wt%, respectively. Tannic acid solution was added to the quaternary ammonium cellulose solution, wherein the mass ratio of quaternary ammonium cellulose to tannic acid was 1:3. The mixed solution was stirred evenly overnight, and the precipitated hydrogel was collected. The hydrogel was pre-frozen at -10--20 °C for 48 h to obtain a pre-frozen hydrogel, which was placed in a freeze dryer and freeze-dried for 20-24 h at a temperature of -50--60 °C and a vacuum degree of 10-20 Pa to obtain a dry solid, which was ground and sieved to obtain a composite hemostatic powder QT. The hemostatic powder was stored at 4 °C away from light for subsequent use.
[0029] Figure 1 This is a scanning electron microscope picture of the hemostatic powder. We can see the interconnected porous structure, which is beneficial to the concentration of blood and promotes the aggregation of blood cells. Example 2
[0030] This embodiment provides a preparation method of a quaternary ammonium cellulose / polyethylene glycol / tannic acid composite powder. Compared with Embodiment 1, the main difference is that polyethylene glycol is introduced to increase adhesion. The method comprises the following steps:
[0031] Quaternary ammonium cellulose, polyethylene glycol and tannic acid were rapidly stirred at room temperature at a speed of 200-300 r / min for 10-15 min and dissolved in deionized water, respectively, with final concentrations of 2 wt%, 15 wt% and 15 wt%, respectively. The quaternary ammonium cellulose solution and the polyethylene glycol solution were mixed evenly to obtain a precursor solution. Tannic acid solution was added to the precursor solution, wherein the mass ratio of quaternary ammonium cellulose / polyethylene glycol / tannic acid was 1:1:3. The mixed solution was stirred evenly overnight, and the precipitated hydrogel was collected. The hydrogel was pre-frozen at -10--20 ℃ for 48 h to obtain a pre-frozen hydrogel, which was placed in a freeze dryer and freeze-dried for 20-24 h at a temperature of -50--60 ℃ and a vacuum degree of 10-20 Pa to obtain a dry solid, which was ground and sieved to obtain a composite hemostatic powder QTP. The hemostatic powder was stored at 4 ℃ away from light for subsequent use.
[0032] Figure 2 This is a scanning electron microscope picture of the hemostatic powder. It can be seen that the pore size of the hemostatic powder is significantly smaller than that of the powder in Example 1. This is because the polyethylene glycol and tannic acid are physically cross-linked to form a strong molecular network with an increased degree of cross-linking. Example 3
[0033] This embodiment provides a method for preparing a quaternary ammonium cellulose / polyethylene glycol / montmorillonite / tannic acid composite powder. Compared with Embodiment 2, the main difference is that amination of montmorillonite is introduced to enhance the hemostatic effect. The method comprises the following steps:
[0034] The aminated montmorillonite powder was evenly suspended in deionized water and ultrasonically dispersed at a power of 100-200 W for 30 minutes to ensure that the aminated montmorillonite powder was evenly dispersed to obtain a 2% montmorillonite suspension. Quaternary ammonium cellulose, polyethylene glycol, and tannic acid were dissolved in deionized water, respectively, with final concentrations of 2 wt%, 15 wt%, and 15 wt%, respectively. The quaternary ammonium cellulose solution, polyethylene glycol solution, and montmorillonite suspension were mixed evenly to obtain a precursor solution. Tannic acid solution was added to the precursor solution, wherein the mass ratio of quaternary ammonium cellulose / polyethylene glycol / montmorillonite / tannic acid was 1:1:1:3. The mixed solution was stirred evenly overnight, and the precipitated hydrogel was collected. The hydrogel was pre-frozen at -10 to -20 °C for 48 h to obtain the pre-frozen hydrogel, which was placed in a freeze dryer and freeze-dried for 20 to 24 h at a temperature of -50 to -60 °C and a vacuum degree of 10 to 20 Pa to obtain a dry solid, which was ground and sieved to obtain the composite hemostatic powder QTPM. The hemostatic powder was stored at 4 °C away from light for subsequent use.
[0035] In this embodiment, quaternary ammonium cellulose, polyethylene glycol and amino montmorillonite constitute a matrix network, tannic acid acts as a physical cross-linking agent to provide interface adhesion, and the strong non-covalent reversible physical interaction between molecules and the movement of polymer chains after hydration of the hemostatic powder give the hemostatic powder self-gelling properties.
[0036] Figure 3 This is a scanning electron microscope picture of the hemostatic powder. It can be seen that the pore size of the hemostatic powder is further reduced. This is because after the addition of amino montmorillonite, the cross-linking degree is further increased and the pore size of the hydrogel is further reduced. Example 4
[0037] The hemostatic powders QT, QTP and QTPM obtained in Examples 1, 2 and 3 were subjected to a tissue adhesion experiment. The experimental steps are as follows:
[0038] The hemostatic powders QT, QTP and QTPM obtained in Examples 1, 2 and 3 of the present invention were subjected to tissue adhesion experiments, and the adhesion performance of the hemostatic powders on pig skin on a 50 N sensor was studied using a general electromechanical testing machine (WDW-05, Spey, China). Fresh pig skin was washed with deionized water and ethanol. After drying with absorbent paper, the treated pig skin was cut into 40 mm×25 mm rectangles for testing. 80 mg of powder was evenly applied to one side of the pig skin, an appropriate amount of PBS was added, and another piece of pig skin was taken to cover the overlapping area of 25×25 mm. Then, the overlapping part of the pig skin was pressed with a weight of 100 g for 5 min, and cured for 5 min at 37°C and 50% humidity. The pig skin was fixed on the tester and a lap shear test was performed at a speed of 5 mm / min until the sample was completely separated.
[0039] A 2 mm diameter indentation was created in the treated porcine skin and the resulting penetrating defect tissue was fixed to the cylinder. The cylinder was connected to a syringe pump and a pressure monitor via a three-way stopcock. The powder was then deposited on the hole to form a hydrogel in situ. After 5 min of hydrogel formation, PBS was gradually injected into the device. The syringe pump was operated at 2 mL min -1 When the seal fails, the burst pressure is used as the critical pressure.
[0040] Specific test results such as Figure 4 The QTP and QTPM hemostatic powders obtained in Examples 2 and 3 have good tissue adhesion and tissue sealing capabilities, among which the QTPM sample obtained in Example 3 has the best tissue adhesion and sealing properties. After spraying 5% urea solution (urea) on the pig skin surface, the adhesion performance is greatly reduced, which is conducive to the subsequent disassembly and removal of the samples. Example 5
[0041] The hemostatic powders QT, QTP and QTPM obtained in Examples 1, 2 and 3 were subjected to antibacterial experiments.
[0042] The present invention uses Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 43300) to detect the antibacterial properties of hemostatic powder. 0.2 g of QT, QTP, and QTPM hemostatic powders are added to 10 ml of liquid culture medium respectively, and after ultrasonic treatment for 2 hours, the solution is incubated at 37°C for 24 hours. Filter and sterilize with a 0.22 μm sterile filter to obtain an extract and store it at -20°C. 10 μL of bacterial solution and 90 μL of extract are added to a 96-well plate, and the final concentration is 1×10 5 CFU / mL, the culture plates were incubated at 37 °C for 20 h, and the absorbance was measured at 595 nm using a microplate reader (iMark, Bio-Rad Laboratories, Inc).
[0043] In this study, the extract obtained in step (1) of Example 5 was mixed with the bacterial solution to obtain a final bacterial concentration of 1×10 5 CFU / mL, incubate at 37°C, 120 rpm for 12 h. Pour the hot agar medium into the bacterial culture dish, cool it until the agar medium solidifies, spread 100 µL of the bacterial suspension on the agar plate, and incubate at 37°C for 12 h.
[0044] Specific test results such as Figure 5 After the extracts of QT, QTP and QTPM hemostatic powders obtained in Examples 1, 2 and 3 were added to the bacterial suspension for incubation, the absorbance of the solutions was significantly reduced; this indicates that after the sample extracts were co-cultured with bacteria, the bacteria were basically inhibited, and the composite hemostatic powder has antibacterial properties. Example 6
[0045] The hemostatic powders QT, QTP and QTPM obtained in Examples 1, 2 and 3 were subjected to in vitro coagulation absorbance detection, and the experimental steps were as follows:
[0046] The hemostatic performance of the powder was further evaluated using the coagulation index, and the procoagulant performance of the different hemostatic powders in the examples was evaluated by monitoring the red blood cells that did not participate in the clot (absorbance at 540 nm). The powder (50 mg) was added to a test tube and preheated at 37 °C for 5 min. 1 mL CaCl2 (0.1 mol L -1 ) was mixed with 9 mL of citrated rabbit blood, and 100 μL of calcium-activated blood was quickly added to the test tube. Incubate at 37°C, 80 rpm for 10 min, then add 10 mL of deionized water and centrifuge at 1000 rpm for 5 min. The absorbance of the supernatant was measured at 540 nm using an ELISA reader (iMark, Bio-Rad Laboratories, Inc).
[0047] Specific test results such as Figure 6 The absorbance of the sample obtained in Example 3 is significantly lower than that of other components, so the composite hemostatic powder has an effective coagulant effect. Example 7
[0048] The hemostatic powders QT, QTP and QTPM obtained in Examples 1, 2 and 3 were subjected to biocompatibility characterization, and the experimental steps are as follows:
[0049] Mouse fibroblast L929 cells were used to evaluate the cytotoxicity of in vitro hemostatic powder. The powder was first sterilized with alcohol and then sterilized by ultraviolet irradiation overnight. The sterilized powder was added to DMEM and incubated at 37°C for 24 h. The hydrogel extract was obtained by filtration sterilization with a 0.22 μm bacterial filter and 1% penicillin-streptomycin and 10% fetal bovine serum. The culture medium was then replaced with the hydrogel extract, and L929 cells were seeded into 96-well plates at a cell concentration of 5000 cells / well per well. After incubation for 24, 48, and 72 h, a certain amount of CCK-8 solution was added to each well. The completed original DMEM was used as a control. After incubation at 37°C for 2 h, the absorbance was measured at 595 nm using a microplate reader (iMark, Bio-Rad Laboratories, Inc).
[0050] The live / dead staining method was used to further evaluate the cytotoxicity of the hemostatic powder. The cell culture medium was replaced by the hydrogel extract. First, L929 cells were seeded into 24-well plates at a density of 10,000 cells per well and incubated for 24, 48, and 72 h, respectively. Then, the cell stain was added and the cells were incubated at 37°C for 30 min under light-protected conditions. Finally, the cell stain was aspirated and images of live and dead cells were taken using a fluorescent cell microscope.
[0051] Specific test results such as Figure 7 , the absorbance of the samples in Examples 2 and 3 was not significantly different from that in the blank group, but the absorbance of the sample in Example 1 was slightly lower than that in the blank group. This may be due to the fact that the hydrogel molecular network in the sample in Example 1 is more dispersed, while the cross-linked network density of the hydrogel in the samples in Examples 2 and 3 is larger and the intermolecular force is stronger. Therefore, the TA in the sample in Example 1 is more easily released when immersed in the cell culture medium, and the high concentration of tannic acid in the extract affects the growth of L929 cells, resulting in its absorbance being lower than that in the blank group. In addition, when the blank group was subjected to cell culture (24, 48, 72h), there was no statistically significant difference in the live and dead staining images of Examples 2 and 3. The results show that the composite hemostatic powder of the present invention has good biocompatibility and can meet the biosafety requirements of hemostatic materials. Example 8
[0052] The hemostatic powders QT, QTP and QTPM obtained in Examples 1, 2 and 3 were subjected to an in vivo hemostatic model experiment, and the experimental steps were as follows:
[0053] In the liver bleeding model, mice were anesthetized and fixed on a surgical board. The liver was exposed through a transverse abdominal incision, and a pre-weighed filter paper was placed under the liver. A 0.5 cm wound was made from the base of the liver lobe with a scalpel to induce bleeding. After free bleeding for ≈5 seconds, 80 mg of different hemostatic materials were deposited on the wound to stop bleeding. Mice that were not treated after bleeding were used as the control group. The blood loss was calculated by weighing the filter paper before and after blood aspiration, and the hemostasis time was recorded.
[0054] In the mouse tail amputation model, anesthetized mice were fixed on a surgical board and pre-weighed filter paper was placed under the mouse tail. 1 / 2 of the mouse tail was cut off with surgical scissors to induce bleeding. After waiting for natural bleeding ≈ 5 seconds, 80 mg of different hemostatic substances were deposited on the cut tail wound to stop bleeding. After hemostasis, the hemostasis time of each group was recorded and the blood loss was weighed.
[0055] Specific test results such as Figure 8 In the liver hemorrhage model, without using any hemostatic material, the mice finally stopped bleeding at 611.67±20.84s (blood loss 81.8±5.81mg). After using the samples of Examples 1, 2, and 3, they stopped bleeding within 156±6.24s, 87.33±7.02s, and 71.67±7.09s, respectively, and the blood loss reached 35.43±3.42mg, 26.03±1.26mg, and 19.23±2.60mg, respectively; in the mouse tail-cut model, the blank group stopped bleeding within 726±64.37s (total bleeding volume was 75.57±9.58mg). After using QT, QTP, and QTPM hemostatic powders, a small amount of blood oozed from the wound surface. QT contacts blood to form a blood clot, and finally stops bleeding at 219±14.01s, 125.33±10.97s, and 91±12s, with the amount of bleeding reaching 38.38±4.83mg, 22.06±1.71mg, and 15.24±1.77mg; therefore, the QTPM hemostatic powder obtained in Example 3 can effectively increase the speed of hemostasis and reduce the amount of bleeding at the wound.
[0056] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of the claims of the present invention, it is protected by the patent law.
Claims
1. A self-gelling antibacterial and adjustable adhesive rapid hemostatic powder, characterized in that: The rapid hemostatic powder consists of quaternary ammonium cellulose, polyethylene glycol, amino montmorillonite and tannic acid, wherein the concentration of the quaternary ammonium cellulose is 2 wt %, the concentration of the polyethylene glycol is 15 wt %, the concentration of the tannic acid is 15 wt %, and the mass ratio of the quaternary ammonium cellulose, the polyethylene glycol, the amino montmorillonite and the tannic acid is 1:1:1:
3. The quaternary ammonium cellulose, the polyethylene glycol and the amino montmorillonite constitute a matrix network, the tannic acid serves as a physical cross-linking agent to provide interface adhesion, and the strong non-covalent reversible physical interaction between molecules and the movement of the polymer chain after the hemostatic powder is hydrated make the hemostatic powder have self-gelling properties; 5 wt % of urea solution can replace the hydrogen bond between tannic acid and polyethylene glycol, resulting in the destruction of the adhesion property.
2. A method for preparing the self-gelling antibacterial and adjustable adhesive rapid hemostatic powder according to claim 1, characterized in that: The precursor solution and the tannic acid solution are mixed, stirred evenly, and left overnight. The precipitated hydrogel is collected, pre-frozen overnight, and placed in a freeze dryer for freezing treatment to obtain a dry solid. The solid is ground and sieved to obtain a composite hemostatic powder. The precursor solution is a mixed solution of quaternary ammonium cellulose, polyethylene glycol, and amino montmorillonite.
3. The method for preparing a self-gelling antibacterial and adjustable adhesive rapid hemostatic powder according to claim 2, characterized in that: The method for preparing the aminated montmorillonite comprises the following steps: adding 3-aminopropyltriethoxysilane to the crushed montmorillonite, stirring until the reaction is complete, adding deionized water to terminate the reaction, washing with deionized water and ethanol alternately, taking out, and drying at 60-80° C. to constant weight to obtain the aminated montmorillonite.
4. The method for preparing a self-gelling antibacterial quick hemostatic powder with adjustable adhesion according to claim 3, characterized in that: When 3-aminopropyltriethoxysilane is added to the crushed montmorillonite, 1 g of montmorillonite corresponds to 5 mL of 3-aminopropyltriethoxysilane.
5. The method for preparing a self-gelling antibacterial quick hemostatic powder with adjustable adhesion according to claim 4, characterized in that: The pre-freezing overnight and freezing treatment in a freeze dryer refers to pre-freezing at -20 to -10°C for 48 hours to obtain a pre-frozen hydrogel, placing it in a freeze dryer, and freeze-drying it for 20 to 24 hours at a temperature of -60 to -50°C and a vacuum degree of 10 to 20 Pa.
Citation Information
Patent Citations
Polyphenol-based medical tissue adhesive as well as preparation method and application thereof
CN114369441A
Preparation method of hemostatic hydrogel containing natural polysaccharide
CN115433371A